PERSEPSI MASYARAKAT SUKU TOGUTIL DALAM PENGELOLAAN HUTAN - Edom Bayau (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
Togutil tribe is one of marginal society which in other context is sometimes referred to as remote society inhabiting East Halmahera forest. The study was conducted to find out the perception of Togutil people in forest management and non-timber forest product utilization which is utilized as their life necessity without damaging the surrounding nature even though their life pattern all depends on nature. This research was conducted for three months from September until December 2017 in northern wasilei district of East Halmahera Regency using qualitative descriptive method. Martodirdjo (1991: 74) who said the purpose of descriptive research is to describe and understand the pattern of behavior of a society as it is in the context of wholeness or a unified whole, and from the results of research shows that the existence of Togutil tribe people view the forest not as a place to meet the needs alone but in their perceptions, the forest must be on guard because it has residents of the ancestors who until the moment masi believed sehingg in the activity of demolition of a land must be preceded by performing rituals as a form of permission application to the ancestors.